PENGARUH PEMANFAATAN TEKNOLOGI SISTEM INFORMASI TERHADAP PENGELOLAAN KEUANGAN PEMERINTAH DAERAH KOTA XYZ - Denny Zaminaldi; Nurhafiani (ADMIN: Jurnal Administrasi Negara, 2024)
The aim of the research is to determine the influence of the use of technology on the management of financial reports in the regional government of XYZ City. The research method used in this research is a quantitative method. The population in this study was 49 Financial Administration Officials (PPK), a sample of 94 PPK. The data sources are primary data obtained through questionnaires from people who have sent their children to school and secondary data from websites, online journals, literature studies, and references related to research. The research variables consist of Information Technology Utilization (X) and Regional Financial Management (Y). Data collection techniques using observation, interviews and documentation. Data analysis techniques are descriptive analysis, validity test, reliability test, multiple linear regression, classical assumption test, hypothesis test. Data was processed using SPSS 0.26. The results of the research show that the use of IT has a positive and partially significant effect on the Financial Management of the Regional Government of XYZ City, where based on the results of testing the third hypothesis it is known that there is a significant influence of the use of IT on the financial management of the Regional Government of XYZ City. This is shown by obtaining a T value of 4.278 with a significance of 0.000 where 0.001 <0.05 so that H0 is rejected and Ha is accepted, namely "there is an influence of IT utilization on the financial management of the Regional Government of XYZ City". This means that the better use of IT provided to employees, the better the resulting financial management and vice versa. Furthermore, the contribution amount of the Adjusted R Square value is 0.155. This means that the IT utilization variable (X) has a partial contribution of 0.155 or 15.5% to the financial management of the Regional Government of XYZ City (Y).